Constitutional basics of the Second Austrian Republic - E. A. Vodyanitskaya (Московский журнал международного права, 2009)
After the Second World War, Austria, much like Germany, was divided into a British, a French, a Soviet and a U.S. Zone and governed by the Allied Commission for Austria. Largely owing to Karl Renner’s action a Provisional Government was set up on April, 27 1945. The Austrian Government was recognized and tolerated by the Four Powers. On the 15th of May 1955 Austria regained full independence by concluding the Austrian State Treaty with the Four Occupying Powers. On the 26th of October 1955 Austria was declared “permanently neutral” by an act of Parliament, which remains to this day.The political system of the Second Republic came to be characterized by the system of Proporz, meaning that most posts of political importance were split evenly between members of the Social Democrats and the People’s Party. The Proporz and consensus systems largely held up to 1983. The most significant feature of the constitutional principles of Austria since 1955 is that the “permanent neutrality” forms part of the Austrian constitution. In 1995 the country became a member of the European Union and retained its constitutional neutrality.